Academic Performance in Criminalistics Courses of Senior BS Criminology - Alday, Estee Louise; Medios, Ysrael; Rosin, Marlon; Adra, Marry Jane (JPAIR Multidisciplinary Research, 2020)
Researchers are finding the weaknesses and strengths of the students to find the factors to enhance the student’s learning performance at school. This study dealt with the academic performance of Senior BS Criminology students in their criminalistics courses and the activities of 26 males and 24 female students. A descriptive method of research was used in the study. The survey questionnaire was used. Percentage, weighted mean, and ranking of the statistical tools were employed to treat the data. Results show the senior BS Criminology students got above average grades in their criminalistics courses. The identified factors affecting their academic performance were the student and teacher-related factors. Listening attentively, motivation to get high grades, and studying were some of the student-related factors, while mastery of the subject is the topmost factor affecting their performance in terms of teacher-related problems. The students excel in their criminalistics courses, but room for improvement must be made. The academic performance of the students was affected by the relationship between teachers and students in the classroom.
Keywords: Criminology; Academic performance; criminalistics courses; descriptive method; Daraga; Albay City; Philippines